THE IMPACT OF AUTOMATION TOWARDS FEMALE LABOR FORCE IN INDONESIA AND THE ATTEMPTS TO ESTABLISH BETTER PROTECTION MECHANISM - Virgil, Dominique (PEOPLE: International Journal of Social Sciences, 2019)
In the current era of disruption, automation is considered as the answer of the problem of the decreasing number of workforces which can’t meet the demand of increased productivity for greater growth. Despite the benefit resulted from automation, rapid adaptation of automated technology in various sectors has put thousands of workers under threat on losing their jobs, without any guarantee of a definite substitute job once they have been replaced, especially female workers. The potential of female workers for economic advancement are currently being undermined with less attention given. This paper will discuss whether or not the enhancement of female labor force participation can contribute significantly to the increase of productivity and growth in the disruption era. This paper will also discuss whether or not the existing protection mechanism for female workers is adequate to optimize their potential and at the same time extenuate the adverse effects of automation from a legal and socio-cultural perspectives.